Practising postcolonial pedagogies in higher education teaching and research - Liddy, Mags (Journal of University Teaching and Learning Practice, 2021)
Teaching about global development challenges is a complex and demanding process both for students and teachers. In this article, I examine the potential of postcolonial pedagogies in facilitating the process of learning to unlearn and in developing learners’ agency in reading the world. I focus on two teaching encounters to examine the potential of postcolonial pedagogies; one is a Sustainable Development module, part of a degree programme in formal higher education and the second teaching encounter are preparatory sessions for overseas volunteers.This paper examines the process and implications of utilising postcolonial pedagogies in these settings and is written from my perspective as a self-reflexive teacher and researcher. This form of teaching and learning raises three particular tensions for me: structural concerns in the Irish education system, pedagogical questions as well as personal implications for me as a teacher and my knowledge base. This article concludes with a summary of these identified tensions, outlining continuing questions rather than presenting solutions. Teaching about global development challenges is difficult, challenging and emotional work, demanding vigilance and reflexivity by the teacher.